Chlorophyllin in the intra-uterine development of mice exposed or not to cyclophosphamide - doi: 10.4025/actascihealthsci.v35i2.12470 - Vessia Silva Leite; Rodrigo Juliano Oliveira; Tatiane Yumi Nakamura Kanno; Mario Sergio Mantovani; Estefânia Gastaldello Moreira; Maria José Sparça Salles (Acta Scientiarum. Health Sciences, 2013)
Chlorophyllin, a sodium-copper salt synthesized from chlorophyll, has already proved to have anticlastogenic, antimutagenic and anticarcinogenic activity, however few are the studies in the teratogenicity area. The present study evaluated the effects of chlorophyllin in intra-uterine development of mice exposed or not to cyclophosphamide. Pregnant females were divided into 8 groups of 15 animals each, G01 - PBS (0.1 mL 10.0-1 g) orally; G02 – cyclophosphamide (20.0 mg kg-1) i.p.; G03, G04 and G05 - chlorophyllin at concentrations of (5.0, 10.0 and 15.0 mg kg-1) orally; G06, G07 and G08 (5.0, 10.0 and 15.0 mg kg-1) orally, of chlorophyllin, respectively, and (20.0 mg kg-1) i.p. of cyclophosphamide. In the 18th day the females were submitted to laparotomy and females and fetuses analyzed. The results showed that the chlorophyllin was not effective in protecting the reproductive parameters as well as teratogenicity. Finally, it was observed that the presence of chlorophyllin increased the frequency of some malformations when combined with cyclophosphamide. However, it was not teratogenic and not embryo lethal in this experimental design.